Pd(II) and trinuclear Ag(I) bis-N-heterocyclic carbene complexes: Synthesis, structural and in vitro anticancer activity - Salman, Abbas Washeel; Haque, Rosenani A. (European Journal of Chemistry, 2016)
The synthesis and characterization of two Ag(I)- N-heterocyclic carbene complexes 3 and 4 of imidazole-based NHC proligands 1 and 2, respectively, are described. The findings revealed that the choice of the counter ions is crucial, which can lead to different supramolecular architectures. Complex 3 is a trinuclear, whereas its analogue complex 4 is mononuclear. Despite being structurally different entities, these complexes form cis-palladium-NHC complex 5 by trans-metallation method, which is a cis-platinum analogue. All the reported compounds 1-5 were tested for their anticancer activities, where compounds 2 and 3 found more potent than the rest.